Navigating Nuances: Intermediate Teachers’ Experiences Handling Generation Z Learners - Ladylou B Dejacto; Francis May S Valmorida; Genesis B Naparan (Journal of Elementary and Secondary School, 2023)
Education in the 21st century is centered on equipping new learners with skills relevant to their daily lives, particularly Generation Z learners. As the backbone of the education system, teachers must have the competence and skills to effectively teach and cater to this cohort's unique needs. This study aimed to explore the specific challenges and coping strategies of teachers handling Generation Z learners at the intermediate level. This study employed a phenomenological research design involving twelve (12) intermediate teachers in District 10 of Ozamiz City. Thematic analysis was used to examine the data revealing commonly faced challenges, including Generation Z learners' disruptive behaviour, inappropriate use of technology, and poor academic performance. Furthermore, it was revealed that intermediate teachers use varied coping strategies in handling Generation Z learners. These strategies include the application of proper classroom discipline, partnership between parents and teachers, and enhancing teachers' ICT literacy. The result of this study offers valuable perspectives for teachers, school administration, and policymakers. In conclusion, addressing these challenges can elevate Generation Z learners' learning experiences and improve their academic performance. Furthermore, it encourages teachers to be more innovative and prepared to meet the demands of 21st-century education.